Application of Laser Microirradiation in the Investigations of Cellular Responses to DNA Damage - Kong, Xiangduo; Wakida, Nicole M.; Yokomori, Kyoko (Frontiers in Physics, 2021)
Since the laser has been invented it has been highly instrumental in ablating different parts of the cell to test their functionality. Through induction of damage in a defined sub-micron region in the cell nucleus, laser microirradiation technique is now established as a powerful real-time and high-resolution methodology to investigate mechanisms of DNA damage response and repair, the fundamental cellular processes for the maintenance of genomic integrity, in mammalian cells. However, irradiation conditions dictate the amounts, types and complexity of DNA damage, leading to different damage signaling responses. Thus, in order to properly interpret the results, it is important to understand the features of laser-induced DNA damage. In this review, we describe different types of DNA damage induced by the use of different laser systems and parameters, and discuss the mechanisms of DNA damage induction. We further summarize recent advances in the application of laser microirradiation to study spatiotemporal dynamics of cellular responses to DNA damage, including factor recruitment, chromatin modulation at damage sites as well as more global damage signaling. Finally, possible future application of laser microirradiation to gain further understanding of DNA damage response will be discussed.